Nursing Care For Children With Bronchopneumonia Diagnosion in Flamboyant Treatment Room - Nurmasita, Nurmasita; Sakriawati, Sakriawati; Sri Wahyuningsih; Durratul Fakhriyah; Anriani, Anriani (Universitas Islam Negeri Alauddin Makassar, 2024)
Bronchopneumonia is an inflammation of the respiratory tract that occurs from the bronchi to the alveoli. Bronchopneumonia is more common in young children and infants and is usually caused by the bacteria Streptococcus pneumonia and Hemofilus influenza. The aim of this study is to determine the nursing care and appropriate intervention for patients with a diagnosis of bronchopneumonia. The design of this research is a case study with a nursing process approach. The sample in this study was a child with the initials